Siofor (metformin) administration in the treatment of metabolic syndrome in patients with gout in hospital - V. B. Maximenko; G. N. Provotorova; D. I. Lahin; I. A. Volkoresov; V. P. Li; V. I. Suhinin; S. M. Ryabova (Научно-практическая ревматология, 2016)
Objective. To assess efficacy of hyperuricemia and other metabolic syndrome (MS) features treatment with siofor in patients with gout in hospital.Material and methods. 50 male pts with gout (mean age 54,5±2,0 years) were included. Diagnosis of gout fulfilled recommendations of S. Wallace et al [14]. MS was diagnosed according to common criteria. All pts were examined at admission and after completion of hospital treatment. Height, weight, waist and thighs circumference, skin fold thickness above triceps muscle and blood pressure were measured. Body mass index, waist circumference/thighs circumference (WC/TC) index were counted. Uric acid (UA), triglycerides, cholesterol, glucose, creatinine and urea blood concentration was evaluated. 13 pts without contraindications and anti-gout therapy were treated with siofor.Results. Hyperuricemia was present in 72,9% of gout pts with MS. UA concentration correlated with somatic and laboratory features of MS. Hospital treatment with siofor provided significant decrease of UA concentration and tendency to decrease triglycerides and cholesterol. Somatometric features of MS did not change.Conclusion. Administration of siofor in hospital is a necessary initial stage of long term gout therapy with medications decreasing insulin resistance. This stage should include choice of effective dose of the drug, assessment of its tolerability, evaluation of possibility of otherMS features correction.